Antixenosis and tolerance to Diabrotica speciosa (Coleoptera: Chrysomelidae) in common bean cultivars - Boica Júnior, Arlindo Leal [UNESP] (2015)
Diabrotica speciosa (Germar, 1824) (Coleoptera: Chrysomelidae) is a polyphagous insect pest that attacks several crops of agricultural importance including common beans (Phaseolus vulgaris L.; Fabales: Fabaceae). Diabrotica speciosa larvae feed on the plant root system whereas the adults are leaf defoliators. Diabrotica speciosa control relies mainly on pesticide applications resulting in ecosystem contamination and other problems. This research aimed to identify common bean cultivars that express antixenosis to D. speciosa adult feeding and/or tolerance to larval injury, as well as to determine the resistance levels of the cultivars. To evaluate antixenosis, 10 common bean cultivars were tested for D. speciosa adult feeding preference in free-choice and no-choice tests. The cultivars were 'IAC-Una', 'Diamante Negro', 'IAC-Diplomata', 'FT-Nobre', 'Ônix', 'IAC-Uirapuru', 'IPR-Tiziu', 'BRS-Explendor', 'IAC-Maravilha' and 'BRS-Supremo'. Then, 6 cultivars were selected from the adult feeding assay and used in tests that assessed their tolerance to injury by D. speciosa larvae. In the free-choice test, the cultivars 'IAC-Una' and 'IAC-Uirapuru' were the least preferred by D. speciosa adults for feeding, whereas the cultivars 'IAC-Diplomata' and 'Ônix' were the least preferred in the no-choice test. The 'Ônix' and the 'IAC-Una' cultivars had the lowest reductions in plant height and dry weight of the aerial part after injury by D. speciosa larvae; the cultivars 'BRS-Explendor' and 'IAC-Diplomata' had intermediate reduction percentages; and the other cultivars were susceptible to injury by D. speciosa larvae. Field studies should evaluate the performance of the cultivar 'Ônix' infested with adults and larvae of D. speciosa in order to confirm the promising results obtained in the current study under laboratory and greenhouse conditions.